Learning and decision making along a nutritional gradient - Katz, Keziah, author; Naug, Dhruba, advisor; Hoke, Kim, committee member; Kondratieff, Boris, committee member; Pratt, Stephen, committee member (Colorado State University. Libraries, 2019)
Nutrition is fundamental to the life history of all animals and the behavioral processes by which animals acquire nutrition are of central interest to students of animal behavior. How an animal learns about available food resources, and the strategies adopted to acquire food resources are therefore of central importance. While animal nutrition is quite complex, energy is a fundamental nutrient and is the focus of this work. In chapter 1, honeybees were fed or starved before they were given a choice assay to determine how individual energetic state altered their choice between gathering information about food resources and consuming known food resources. It was found that bees which were relatively satiated prioritized the collection of information over energy. This work was expanded in chapter 2, in which the energetic states of honeybee colonies were manipulated, in addition to the manipulation of individual energetic state. This experiment provided insights into how group members make decisions in the presence of conflicting individual and group level interests and found that honeybee behavioral phenotypes vary in how they prioritize group and individual needs. The first two chapters focus on how animals make decisions after they have acquired some information, but differences in learning also play a vital role in the acquisition of nutrition. In chapter 3, bees were weighed early and late in their lifetimes, and it was found that bees with more stable weight percentile ranks performed better in a learning assay than bees with unstable weight percentile ranks. As nutritional environment plays a significant role on the body weight of individuals, this may indicate that consistent nutritional conditions contribute to bee cognition. Along with nutrition, body weight is also correlated with the metabolic rate of individuals. Metabolic rate is directly tied to the energy acquisition behavior of animals, as it determines how and at what rate energy is processed by an animal. In order to evaluate how metabolic rate alone influences nutrient acquisition, a model, presented in Chapter 4, was constructed that evaluated the performance of different metabolic rates in different nutritional environments. In general, high metabolic rates were more favorable in rich nutritional environments and low metabolic rates were more favorable in poor nutritional environments. It was also shown that diversity of metabolic rates within a group is advantageous in some environments. Taken together, this work indicates that nutrition, in the form of energy, plays a vital role in the how animals learn and make decisions. This is true for nutrition at both the individual and group level, over immediate and long-term timescales, and for physiological differences in the capacity of an animal to assimilate energy. These findings have broad implications in behavioral ecology and are discussed in terms of optimal foraging, group behavior, developmental plasticity, and gene-environment interactions.
Keywords: behavior; decision; nutrition; choice; bee; energetics